Preliminary experience with recanalization of large vessel occlusion due to underlying long-segment dissection using a standby microwire technique - Zhang, Xiaoxi; Xu, Hongye; Feng, Zhengzhe; Hua, Weilong; Shen, Hongjian; Zhang, Lei; Zhang, Yongxin; Xing, Pengfei; Yang, Pengfei; Xu, Xiaolong; Li, Zifu (Frontiers in Neurology, 2022)
Purpose This study aimed at investigating a novel standby microwire technique to facilitate revascularization of large vessel occlusion due to underlying long-segment dissection. Methods Patients with acute ischemic stroke with emergent large vessel occlusion (ELVO) due to underlying long-segment dissection were screened from the prospectively established database between January 2021 and May 2022. The clinical and radiological data of eligible patients who underwent endovascular treatment by using a standby microwire technique were investigated. Results Of the 165 acute ischemic stroke patients who underwent mechanical thrombectomy, the standby microwire technique was used in five patients aged 33–55 years old with occlusion due to underlying long-segment dissection. Of them, three patients were diagnosed with tandem lesions and three were located at the anterior circulation. A 300 cm exchange microwire was used as the standby microwire. Stent deployment was performed in all five patients. Groin puncture to reperfusion time ranged from 10–68 min. Technical success and favorable clinical outcomes were achieved in all five patients (100%). No technique-related complication was observed. Conclusion Our preliminary experience showed that the standby microwire technique was a useful ancillary approach to facilitate the revascularization of large vessel occlusion due to underlying long-segment dissection.